Resolution of HLA‐B*44:02:01G, ‐DRB1*14:01:01G and ‐DQB1*03:01:01G reveals a high allelic variability among 12 European populations. Issue 5 (11th September 2014) - Vidan‐Jeras, B.; Buhler, S.; Dubois, V.; Grubic, Z.; Ivanova, M.; Jaatinen, T.; Ligeiro, D.; Lokki, M.‐L.; Papasteriades, C.; Poli, F.; Spyropoulou‐Vlachou, M.; Tordai, A.; et al.
Abstract Within the framework of the EU‐funded HLA‐NET action, an analysis of three G‐group alleles, HLA‐B*44:02:01G, DRB1*14:01:01G and DQB1*03:01:01G, was undertaken in 12 European populations. Ambiguities were resolved by polymerase chain reaction‐sequence‐specific amplification (PCR‐SSP) or PCR‐sequence‐based typing (PCR‐SBT) in a total of 5095 individuals. The results of the DRB1*14:01/14:54 ambiguity showed high relative ratios (24–53%) of DRB1*14:01 in Bulgarians, Croatians, Greeks, Italians and Slovenians, contrasting with low ratios (6–13%) in Austrians, Finnish, French, Hungarians, Norwegians and Swiss. Resolution of the B*44:02/44:27 ambiguity showed that B*44:27 had a high relative ratio in Slovenians (25.5%) and Bulgarians (37%) and low in French and Swiss (0.02–1%), and was not observed in Greeks and Italians. The highest relative ratio of DQB1*03:19 was found in Portuguese (11%), by contrast with low ratios (0–3%) in the other five populations. Analysis of the A, B, DRB1 phenotypes and family‐derived haplotypes in 1719 and 403 individuals positive for either HLA‐B*44:02G or DRB1*14:01G ambiguities, respectively, showed some preferential associations, such as A*26∼DRB1*14:01, B*35∼DRB1*14:01, B*38∼DRB1*14:01 and B*44:27∼DRB1*16. Because these ambiguities are located outside the peptide‐binding site, they may not be recognized by alloreactive T‐cells. However, because of strong linkage disequilibrium (LD), the DRB1*14:01 vs DRB1*14:54 and the B*44:02 vs B*44:27 mismatches are associated to DRB3‐, and C‐mismatches, respectively. These results are informative for algorithms searching unrelated hematopoietic stem cell donors. For B*44:27‐positive patients, searches are expected to be more successful when requesting donors from Southeastern‐European ancestry. Furthermore, the introduction of human leukocyte antigen (HLA)‐typing strategies that allow resolving exon 4 (for class I) and exon 3 (for class II) polymorphisms can be expected to contribute significantly to population genetics studies.